Application of advanced volumetric non-destructive evaluation methods for the analysis of friction welded tube-to-tube plates using an external tool. (2020) - Deepesh, V.; Purushothaman, Amal V.; Muthukumaran, S.; Sastikumar, D.
Abstract: Friction welding of tube-to-tube plate using external tool (FWTPET) is a novel variant of friction welding process for joining tubes to tube plates. This process has the capability of producing leak proof joints between similar or dissimilar materials. Being a solid state welding process FWTPET has a significant advantage that it is free from fusion related defects usually seen in conventional tube to tube plate joining alternatives which use fusion welding methods. Hence this process offers a strong potential for applications in several sectors including automotive, marine, aerospace etc. However, in order to establish FWTPET for industrial applications it is required to develop suitable Non-Destructive Evaluation (NDE) methods for detection and characterization of the defects. In this study, the defects in FWTPET joints welded between 6 mm thick AA 6061 plate and 2 mm thick AA 1060 tube under various conditions are investigated using two advanced volumetric NDE methods, namely Digital Radiography (DR) and Phased Array Ultrasonic Testing (PAUT). This study shows the capability of these volumetric NDE methods to assess the quality of FWTPET joints, and to reveal significant information about the conditions which lead to defect formation. This work also brings out the effect of the parameters of FWTPET using theoretical model and NDE results, and in turn suggests the parametric combinations which could offer defect free joints.